Late Pleniglacial – Late Glacial climate oscillations detected in the organic lacustrine succession at the Lipowo site, north‐eastern Poland. (7th October 2022) - Rychel, Joanna; Sokołowski, Robert J.; Sieradz, Dominika; Hrynowiecka, Anna; Mirosław‐Grabowska, Joanna; Sienkiewicz, Elwira; Niska, Monika; Szymanek, Marcin; Zbucki, Łukasz; Ciołko, Urszula; Rogóż‐Matyszczak, Anna
Abstract: The profile of the Lipowo palaeolake (NE Poland) preserves a record of environmental and climate changes from the Last Glacial Termination (16.5k cal ka BP), stretching from the Oldest Dryas to the youngest Allerød warm oscillation. In this interdisciplinary study of the lacustrine succession at Lipowo, we used biological and geochemical indicators and multiproxy analyses to reconstruct environmental changes in the lake ecosystem, such as mollusc, zooplankton and vegetation development, trophic state, water temperature and water level. Four cold and four warm climate oscillations of different durations were identified on this basis: the Older Dryas climate deterioration and two short‐term coolings within the Allerød Interstadial, separated by warm periods in the Bølling and Allerød. The covering of the lake series by diamicton deposits from the melting of dead‐ice blocks is a particularly interesting and rare phenomenon for a postglacial area. The hydrological system of the catchment was generally closed, with a periodically opening and existing flow‐through lake. Over the period of the lake's existence, vegetation changed in general from steppe tundra to forest with birch and pine. For most of this time, the palaeolake was mainly oligotrophic, with increased productivity and a higher trophic level only notable during the middle Bølling.